Propuesta para el manejo de materias primas, insumos y líneas de servicio en el proceso productivo de una empresa de bebidas gaseosas (2019)
To carry out the objective, the current situation of the company was initially diagnosed by carrying out an inventory through a matrix of the chemicals used in the production process, jointly constructed flow diagrams to understand and recognize the operation and needs of the plant identifying critical points with opportunity for improvement. Subsequently, chemicals were evaluated for their impact on the process in terms of quality, safety, health and costs, thus selecting the substances with the highest potential for improvement, of those resulting in Liquid Nitrogen, Sodium carbonate, Sodium hydroxide and Carbon dioxide.